Microtus longicaudus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Microtus longicaudus (Merriam, 1888). Am. Nat., 22:934. REVIEWED BY: R. E. Barry, Jr. (REB). TYPE LOCALITY: U.S.A., South Dakota, Custer Co., Custer (Black Hills), 5500 ft. (1676 m). DISTRIBUTION: Rocky Mtns., from N. Yukon and E. Alaska south to S. New Mexico and Arizona, and adjacent foothills and plains; east to W. South Dakota; west to N.W. Pacific Coast (U.S.A.). COMMENT: Subgenus Chionomys, as in Anderson, 1960; or Microtus (— Arvalomys), as in Chaline, 1974, and Gromov and Polyakov, 1977:317. This widespread species is in need of taxonomic revision (SRL). Revised in part by Long, 1965, Univ. Kans. Publ. Mus. Nat. Hist., 14:493-758. Probably includes coronarius, an insular derivative (RSH, SRL). ISIS NUMBER: 5301410008080021001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 493, DOI: 10.5281/zenodo.7353034